Highly Secured Encryption for Accessing Data in the Cloud Environment - Rishabh Bhutani, Srinivasan Sriramulu, M. Thirunavukkarasan (International Journal of Advanced Science and Technology, 2020)
The computing world has transformed a lot with the evolution of computing models and basic database services like storing, updating and fetching records in such a way that any organization or company is able to do and maintain their work efficiently and achieve their desired result in an efficient manner. The main matter of interest in cloud databases is data security. To secure the data in cloud databases higher degrees of privacy and authentication is required. One of the important methods for providing security is cryptography. Cryptography is one of the major methods for providing security. Many symmetric and asymmetric algorithms are provided by cryptography for securing data. Dissimilar keys are used in asymmetric algorithms whereas identical keys are used in symmetric algorithms for encoding and decoding purposes. In this paper symmetric cryptographic algorithms namely Advanced Encryption Standard and Data Encryption Standard will be represented and compared. They are based on many substitutions, permutation and transformation. The final result shows that AES is better than DES for providing security to bigger files.